The American Economic Problem - James K. Galbraith (Intervention. Zeitschrift fuer Ökonomie / Journal of Economics, 2004)
First paragraph: At present writing in early 2004, nearly nine million Americans remain unemployed. Millions more are underemployed, and most of all, underpaid. Forty-four million lack health insurance. Our schools, colleges, universities, roads, water systems, power lines are in decay – and the funds required to repair and expand them are being cut. Not least, we are in a war with no end in sight. That is our economic problem.
Keywords: 330